Synergism of Fe and Al salts for the coagulation of dissolved organic matter: Structural developments of Fe/Al-organic matter associations - Chen, Kai-Yue; Liu, Yu-Ting; Hung, Jui-Ting; Hsieh, Yi-Cheng; Tzou, Yu-Min (Chemosphere (Oxford), 2023)
Dissolved organic matter (DOM) is distributed ubiquitously in water bodies. Ferric ions can flocculate DOM to form stable coprecipitates; however, Al(III) may alter the structures and stability of Fe-DOM coprecipitates. This study aimed to examine the coprecipitation of Fe, Al, and DOM as well as structural developments of Fe-DOM coprecipitates in relation to changes in Fe/Al ratios and pHs. The results showed that the derived Fe/Al/DOM-coprecipitates could be classified into three categories: (1) at pH 3.0 and 4.5, the corner-sharing FeO6 octahedra associated with Fe–C bonds with Fe/(Fe + Al) ratios ≥0.5; (2) the Fe–C bonds along with single Fe octahedra having Fe/(Fe + Al) ratios of 0.25; (3) at pH 6.0, the ferrihydrite-like Fe domains associated with Fe–C bonds with Fe/(Fe + Al) ratios ≥0.5. At pH 3.0, the Fe and C stability of the coprecipitates increased with increasing Al proportions; nonetheless, pure Al-DOM coprecipitates were unstable even if they exhibited the maximum ability for DOM removal. The associations of Al-DOM complexes and/or DOM-adsorbed Al domains with external surfaces of Fe domain or Fe-DOM coprecipitates may stabilize DOM, leading to lower C solubilization at pH 4.5. Although the preferential formation of Fe/Al hydroxides decreased Fe/Al solubilization at pH 6.0, adsorption instead of coprecipitation of DOM with Fe/Al hydroxides may decrease C stabilization in the coprecipitates. Aluminum cations inhibit DOM releases from Fe/Al/DOM-coprecipitates, promoting the treatment and reuse efficiencies of wastewater and resolving water shortages. This study demonstrates that Al and solution pH greatly affect the structural changes of Fe-DOM coprecipitates and indirectly control the dynamics of Fe, Al, and C concentrations in water. [Display omitted] •Solution pH and Al affect greatly the structural changes of Fe-DOM coprecipitates.•Al-DOM coprecipitates are unstable even if exhibit the maximum DOM removal at pH 3.•C associated with mixed and homogeneously distributed Fe/Al can form stable FAC.•Al is an important cation controlling the C dynamics in water systems with Fe.